The Role of Farmer Groups in Improving Farmer Welfare as a Business Group in Nagari Aripan, X Koto Singkarak District, Solok Regency - Yusmi Nelvi; Helmayuni Helmayuni; Mahmud Mahmud; Delsi Afrini; Edi Firnando; Mardianto Mardianto; Harissatria Harissatria (Baselang, 2023)
The respondents used in this research were the purpose sampling method and simple random sampling. The number of samples taken was 20% of the population of farmer groups, so the total sample was 84 farmers. The analysis technique in this research uses a qualitative descriptive research type using qualitative and quantitative analysis. The research results show that in improving the welfare of farmers, farmer groups act as learning class units, cooperation units and production and farming units which have a very good impact on the farmer groups themselves. The problem faced by farmers as a learning unit is that there are still farmer groups participating in groups. As a cooperative unit, the division of tasks within farmer groups is not realized properly. As a production and farming unit, the farming process is disrupted by weather and unsupportive farming facilities.